1973
DOI: 10.2172/4525217
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of airborne radioactivity. Progress report, January--June 1972.

Abstract: Radiolytic desorption tests of a series of carbon samples containing KI 3 , KI, triethylenediamine (TEDA), or combinations of TEDA and KI showed that a 10 x 16 mesh coconut shell carbon containing 1% TEDA, 2% KI,and a proprietary flame retardant retained iodine better than all products tested except those containing higher TEDA concentrations.Ignition temperature measurements on the same series of samples showed that the 1% TEDA -2% KI product has an ignition temperature of about 330°C under SRP flow condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, it does not do inline ozone assimilation (Hersbach et al, 2020). The rainfall forecasts over Australia are verified against the BoM's Australian Gridded Climate Data (AGCD; Jones et al 2009;Evans et al 2020).…”
Section: Data Forecast System and Experimental Designmentioning
confidence: 98%
“…However, it does not do inline ozone assimilation (Hersbach et al, 2020). The rainfall forecasts over Australia are verified against the BoM's Australian Gridded Climate Data (AGCD; Jones et al 2009;Evans et al 2020).…”
Section: Data Forecast System and Experimental Designmentioning
confidence: 98%
“…Previous data indicated that with one reactor room exhaust header open, only two compartments received 95% of the reactor room flow. 11 Filter pluggage test data were evaluated assuming different numbers of compartments on line and either equal distribution of steam-air-iodine flow to all compartments or steam-air-iodine flow through only two of the on-line compartments.…”
Section: Ventilation and Confinement System Conditionsmentioning
confidence: 99%